Availability of ergonomics requirements in Deanship of Library Affairs in Princess Nora bint AbdulRahman University - ALHammad, Amjad Ibrahim; Agwa, Ahmed Mohammed Fathi (Journal of Economic, Administrative and Legal Sciences, 2022)
The recent study goals to determine the availability of the requirements of the field of work surroundings and its sub-axe, Organizational structure and training, and incentives and rewards, and technology - working conditions in Deanship of Library Affairs in Princess Nora bint AbdulRahman University.The researcher used the descriptive analytical method; the questionnaire was used as a tool to collect information and data related to this study.The results of the study were that the availability of the technology requirements axis, which came first among the axes of the work environment with an average of (3.83), an average indicates the availability of the technology requirements axis to a high degree, The availability of the training requirements axis which came in second place among the working environment axes with an average of (3.80) This is an average indicating a high degree of training requirements, Availability of the organizational structure requirements, which came in third place among the working environment with an average of (3.66) This is an average indicating the high level of organizational structure requirements, Availability of the requirements of the working conditions, which ranked fourth among the axes of the work environment with an average of (3.51) This is an average indicating the high availability of the requirements for working conditions, The availability of the incentive and rewards requirements axis which came in fifth place among the working environment axes with an average of (3.17) This refers to the average availability of the incentive and remuneration requirements.The study recommended the need to take into account the objectivity and the application of justice in the granting of incentives and rewards to employees, And The university administration should focus on the preparation of the incentive system accurately and clearly and work on linking with the performance of the employee and the productivity of work, and Encourage employees to present their new ideas and reward them morally and financially, and to provide all the necessary insurance for employees in the event of accident during the performance of their work.
Keywords: organizational structure; working conditions; incentives and rewards; work environment conditions; technology requirements